[tex]g(3) = -12[/tex]
Step-by-step explanation:
Here we have ,
[tex]g(1) = 4\\g(2) = -3[/tex]
g(n) = g(n − 2) · g(n-1) . We need to find g(3) . Let's find out:
Let's put n=3 , in equation g(n) = g(n − 2) · g(n-1) or , [tex]g(n) = g(n - 2) (g(n-1))[/tex]
⇒ [tex]g(n) = g(n - 2) (g(n-1))[/tex]
⇒ [tex]g(3) = g(3 - 2) (g(3-1))[/tex]
⇒ [tex]g(3) = g(1) (g(2))[/tex]
But , [tex]g(1) = 4\\g(2) = -3[/tex] putting value of this in above equation we get:
⇒ [tex]g(3) = g(1) (g(2))[/tex]
⇒ [tex]g(3) =4(-3)[/tex]
⇒ [tex]g(3) = -12[/tex]
Therefore, [tex]g(3) = -12[/tex] .